Kemampuan Membaca Memahami Dongeng (Märchen) - Silfani Gamrin; Syukur Saud; Wahyu Kurniati Asri (Phonologie : Journal of Language and Literature, 2022)
Abstract. This study aims to determine the ability to read and understand German fairy tales and the factors that influence the ability to read and understand German fairy tales in class XI SMA Negeri 8 Makassar. This study uses a quantitative descriptive method. The technique of collecting data is using written test instruments and questionnaires. Data analysis using percentage technique. The population in this study were all students of class XI MIPA at SMA Negeri 8 Makassar which is consisted of 4 classes with a total of 142 students. The sample in this study were students of class XI MIPA 6 as many as 35 students who were selected (purposive sampling). The results of this study indicated that the ability to read and understand German fairy tales in class XI MIPA 6 SMA Negeri 8 Makassar was 84% or very good category.Keywords: Ability, Reading Comprehension, German Fairy Tales